PENGARUH KEPEMIMPINANTERHADAP KOMITMEN DAN KINERJA GURU MADRASAH TSANAWIYAH PADAPONDOK PESANTREN DI KOTA MATARAM - Birruni, Muhammad (Jurnal Magister Manajemen, 2015)
This study aims to reveal the influence of leadership on organization commitment and the performance of Islamic Junior High School (MTs) teachers in boarding school in Mataram city. The study populations consisted of 358 fully-employed teachers who worked in Islamic Junior High Schools of Pondok Pesantren (Boarding Schools) in Mataram City. By using Slovin formula, the researcher took 79 teachers as the study samples. The study employed a research instrument in the form of a questionnaire containing question related to the variables under investigation, i.e. leadership, organizational commitment and teacher performance. The data were analyzed by using SPSS path analysis. The result of this study reported that there was positive and significant impact of leadership on organizational commitment and the Performance of the Islamic Junior High School techers at the Pondok Pesantren being investigated in Mataram city. Result of the study suggest that to improve the performance of the Islamic Junior High School teachers, school leaders are adviced to keep exercising their leadership skills and commitment to her organization. Kata Kunci: Kepemimpinan, Komitmen Organisasi, Kinerja, dan Analisis Jalur.